“Ensayo de comprobación de 15 lineas promisorias de frijol común (phaseolus vulgaris L.), de exportación en el Bajo Mayo- San Martín” - Gonzáles Ramírez, Roy Rogers (2005)
Confirmation of 15 promissory Lines of Common Sean (Phaseolus vulgaris L.), of export in the First floor May San Martín has as objectives: To select experimental lines of bean in confirmation rehearsal with grain types required by the interna! and externa! market, of good yield potential under the conditions agroecológicas of the First floor May and to Carry out the economic analysis of the best treatments by means of the relationship benefits cost. The investigation work was taken 1 end up in the lands of the Experimental Station The Future", to 14,50 Km. of the city of Tarapoto, south highway Fernando Belaúnde Terry, in a period of 3 months. Located geographically: South latitude 06°30', Longitude west of 76°19' and an Altitude 230 m.s.n.m.m. political Location: Place E.E. El Porvenir", District of Juan Guerra, County and Region San Martín. A Design of Complete Blocks was used at random with 16 treatments (lines) and 3 repetitions, the used lines were DOR 703, ROSINHA DE MOIT, FROM RIO DE JANEIRO, IAPAR MD 821, JAMAPA, LM 93203304, AFR 663, LM 93203246, DOR 719, JU 93-19, GRYPHON, TB 94-01, DOR 797, HR 20, DOR 801 and YELLOW TARAPOTO (witness). The results hurtled that the fine JU 93-19 with 3 165,60 Kg/Ha reached the biggest yield, likewise it demonstrated to be the most precocious reaching the floración to the 38,56 days: 63,36 days to the physiologic maturity and 75,34 days to the crop. The biggest net utility was obtained with the T7 (AFR 663), with 4 126,48 new suns with a benefit cost of 2,94 and the smallest utility the T4 (IAPAR MD 821) with 643, 17 new suns with a benefit cost of 1,28. Almost all the lines overcame in yield to the Yellow Fríjol Tarapoto (Witness) except the line HR 20.